Elucidation of apoptotic pathway on human breast adenocarcinoma cell lines mediated by labisia pumila var. alata extract / Muhammad Faiz Zulkifli - Zulkifli, Muhammad Faiz (2019)
Labisia pumila, or locally known as Kacip Fatimah were widely used by women in Malaysia to treat post-partum illnesses. Due to the increase uses of complementary medicine in breast cancer patient, this herbaceous shrub has been exploited as a replacement to the conventional therapies. Many studies indicated that Labisia pumila exerts a wide range of biological activities, including the anti-proliferation effect. However, details of the mechanism were still poorly understood. Therefore, this study was conducted to elucidate the mechanism of Labisia pumila var. alata (Lpva) inducing anti-proliferative effect towards breast adenocarcinoma (MCF-7) cell lines and the underlying mechanism. The treated cells were subjected to viability assay (MTT assay), apoptosis assay (Flow cytometry), and protein expression (Western blot). Moreover, Lpva was also tested for its estrogenic activity (Molecular docking and estrogen binding assay). Aqueous extracts from Lpva showed anti-proliferative activities in a dose- and time-dependent manner (p>0.005). Flow cytometry analysis showed that the anti-proliferative effect of Lpva induced through the apoptosis pathway where the early apoptotic cell population increase from 20 % in 24 hours to 50% in 72 hours. Molecular docking simulation showed that Lpva phytochemical able to bind to estrogen receptors with diadzein gives the lowest affinity at -9.1 for both estrogen receptors alpha and beta, while estrogen binding assay proved that aqueous extract of Lpva able to bind to estrogen receptor alpha and estrogen receptor beta. Furthermore, estrogen antagonist, fulvestrant (ICI 182,780), proved that Lpva aqueous extract exerts their anti-proliferative effect through the estrogen receptors of MCF-7 cells. Western blot analysis showed that Lpva extracts induced apoptosis through both intrinsic and extrinsic pathways. Lpva significantly increase the expression of caspase 8 and 9 at IC50 and IC75 concentration with caspase 9 showed the highest expression (1.47 protein ratio at IC50 and 1.57 protein ratio at IC75) (p>0.01). Western blot analysis also suggested that Lpva down-regulated the expression of Bcl-2 at IC75 (0.38 protein ratio) and up-regulated the expression of pro-apoptotic protein Bax at IC50 and IC75 (0.64 and 1.14 protein ratio) (p>0.01). These results elucidate the mechanism of Lpva anti-proliferative effect on MCF-7 cells.